Analisis Rasio Keuangan yang mempengaruhi Harga Saham Perusahaan Publik - Ade Putri Nabilah; Erika Jimena Arilyn (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
The purpose of conducting this research is to analyze whether the financial ratio variables contained in this study affect the stock prices of public companies in the consumer goods sector listed on the Indonesian Stock Exchange in 2010-2021. The variables studied are earnings per share, total asset turnover, current ratio, debt to equity ratio, return on assets and price earning ratio. In collecting the sample, the technique used was purposive sampling and there were 11 companies that fulfilled the criteria and were analyzed using panel data regression and the best model that had been selected for this study was the fixed effect model. The results of this study indicate that earnings per share, return on assets and price earning ratio have an effect on stock prices and other variables have no effect on stock prices. Hopefully that in future research would add other variables and use more research timeframes in order to provide better results.